The Mathematical Model of Solid Structural Unit Heat Distribution Based on the Cluster Approach - K.D. Evfimko; M.V. Ushcats; A.A. Mochalov (Журнал нано- та електронної фізики)
The solid structural unit heat distribution mathematical model based on the cluster approach according to the heterogeneity of physical parameters: the thermal conductivity, heat capacity, density and temperature, allowing to obtain the scaling matrix corresponding to these values in the stationary state, enabling calculation of the transient processes in any cluster, allowing to obtain the temporal dependence of these quantities in the corresponding coordinate in the direction of heat propagation for crystalline (with known crystal lattice) and amorphous (with known density) microstructures is presented.